Auditor industry specialism and reporting timeliness - Abidin, Shamharir; Ahmad Zaluki, Nurwati Ashikkin (Elsevier Ltd., 2012)
This study investigates whether industry specialist auditors could speed up the audit work using a sample of 873 public listed companies.The multivariate results indicate that industry specialist auditors do not statistically offer faster audit work than non-specialists.In contrast, Big Four firms do perform significant faster audits as compared to their non-Big Four counterparts. Larger companies, companies reporting profits, and financial companies are found to be associated with faster audits.Conversely, companies receiving qualified audit opinions, reporting extraordinary income, and higher in leverage, are associated with longer audit report lags.